2014
DOI: 10.1159/000358705
|View full text |Cite
|
Sign up to set email alerts
|

Biventricular Pacing Cardiac Contractility Modulation Improves Cardiac Contractile Function via Upregulating SERCA2 and miR-133 in a Rabbit Model of Congestive Heart Failure

Abstract: Objective: To compare the effects of biventricular electrical pacing and conventional single-ventricular pacing for cardiac contractility modulation (CCM) on cardiac contractile function and to delineate the underlying molecular mechanisms. Methods: Forty rabbits were divided into four groups before surgery: healthy control, HF sham, HF left ventricular pacing CCM (LVP-CCM), and HF biventricular pacing CCM (BVP-CCM) groups with n=10 for each group. A rabbit model of chronic heart failure was established by lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
0
21
0
Order By: Relevance
“…It has also been reported that CCM has a favorable effect on cardiac remodeling by echocardiography and histological assessment and normalizes expressions of key cytoskeleton proteins and matrix metalloproteinase (MMPs) [13][14][15]. Our previous study has demonstrated that CCM could normalize the expression of SERCA2a/phospholamban and miR-133 in CHF rabbits, which contributes to the multiaspect cardioprotective action of CCM [16].…”
Section: Introductionmentioning
confidence: 89%
See 3 more Smart Citations
“…It has also been reported that CCM has a favorable effect on cardiac remodeling by echocardiography and histological assessment and normalizes expressions of key cytoskeleton proteins and matrix metalloproteinase (MMPs) [13][14][15]. Our previous study has demonstrated that CCM could normalize the expression of SERCA2a/phospholamban and miR-133 in CHF rabbits, which contributes to the multiaspect cardioprotective action of CCM [16].…”
Section: Introductionmentioning
confidence: 89%
“…The rabbit model of CHF induced in the present study was previously described in detail [16]. Briefly, following the induction of anesthesia in rabbit via ear vein administration of 3% sodium pentobarbital at 1 ml/ kg body weight, the thoracic cavity was opened.…”
Section: Model Of Chfmentioning
confidence: 99%
See 2 more Smart Citations
“…Mature miRNAs through pairing to the 3′-untranslated (3′UTR) region to inhibit target genes mRNA translation or promote mRNA degradation [24]. As a class of regulatory molecules, miRNAs participate in many physiological and pathological processes including heart development [25], regeneration [26], hypertrophy [27], contractility [28] and fibrosis [29]. MiRNAs have recently emerged as important regulators of cellular senescence and aging.…”
Section: Mirnasmentioning
confidence: 99%